KEANEKARAGAMAN MIKROORGANISME RHIZOSFER DALAM MENEKAN TINGKAT SERANGAN PENYAKIT BULAI PADA TANAMAN JAGUNG DI KABUPATEN JOMBANG - Paramitha Pasaribu; Herry Nirwanto; Wiwik Sri Harijani (Plumula : Berkala Ilmiah Agroteknologi, 2019)
One of the most constraint factors among corn farmers, which can cause enormous losses to corn farmers in Indonesia is the downy mildew disease. Losses due to this disease can achieve a loss of up to 90%, controlling of plant pathogens is currently still based on the use of synthetic pesticides, whereas the use of synthetic pesticides on a continuous basis can cause various negative impacts. The negative impact of the use of synthetic pesticides is large enough for the environment one of them is the killing of non-target microorganisms such as fungi and antagonistic bacteria located on the ground especially in the rhizosphere of plants.Therefore need to be followed up research on antagonistic fungus/non parasite for plants derived from rooting corn plant, as a control against pathogen infection. The diversity of microorganisms is important in the balanciation of soil ecosystems. This research aimed to find out the relationship of diversity of microorganisms with the level of maize crop disease, and to know the difference the diversity of rhizosphere microorganisms in corn plantations on different land. The relationship between the diversity of microorganisms and the level of maize crop disease attacks the greater the diversity of microorganisms in the corn crop area, the lower the incidence rate of gallbladder disease. Conversely, the lower the number of microorganisms diversity in the corn crop area will be the higher the rate of bouts disease. The highest diversity index was found in Caruban Village of 1.0983, while the lowest diversity index was found in Sumbersari village of 0,5505, and the lowest level of seizure disease was found in Caruban Village 0.96%, while the highest rate of disease was in Desa Sumbersari by 50%.